EFFECTIVE EFFECTIVE STRATEGIES IN CLASSROOM MANAGEMENT TO IMPROVE LEARNING OUTCOMES IN PRIMARY SCHOOLS - Syaifani (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Class management is a series of strategies, actions, and procedures implemented by teachers to create, manage, and maintain an effective and conducive learning environment. Effective strategies in classroom management are essential because they help create a conducive and structured learning environment, which ultimately improves the quality of learning and student learning outcomes. This study aims to understand how good classroom management, through the arrangement of the physical environment, behavior management, the use of varied teaching methods, and effective communication between teachers, students, and parents, can create a conducive learning environment and support student academic achievement. Effective classroom management plays an important role in improving student learning outcomes in elementary schools. This article discusses various strategies that can be implemented by teachers to create a conducive learning environment, including the physical arrangement of the classroom, the application of consistent rules, and the management of student behavior. In addition, the use of varied learning methods, such as discussions, games, and the use of technology, can maintain student interest and facilitate better understanding. Differentiated approaches to teaching, which take into account individual learning needs of students, as well as good communication with parents, help to increase student participation and academic achievement. Good classroom management also emphasizes the importance of enforcing discipline balanced with emotional support, creating a safe and comfortable learning environment. The implementation of effective classroom management strategies contributes to increasing student engagement, motivation, and learning outcomes in elementary schools.